2003
DOI: 10.1007/s00429-002-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cell reactions to axon injury of sensory ganglion neurons: Increase in number of gap junctions and formation of bridges connecting previously separate perineuronal sheaths

Abstract: This study investigated satellite cell changes in mouse L4 and L5 spinal ganglia 14 days after unilateral transection of sciatic and saphenous nerves. The ganglia were studied under the electron microscope in single and serial sections, and by dye injection. Satellite cell responses to axon injury of the neurons with which they are associated included the formation of bridges connecting previously separate perineuronal sheaths and the formation of new gap junctions, resulting in more extensive cell coupling. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 49 publications
4
75
0
3
Order By: Relevance
“…3B). This idea was fully supported by a quantitative electron microscopic study, which revealed a growth of numerous fine processes between SGC envelopes and a 6-fold increase in the number of gap junctions [64,132] (Fig. 5).…”
Section: Plasticity Of Sgcsmentioning
confidence: 71%
See 1 more Smart Citation
“…3B). This idea was fully supported by a quantitative electron microscopic study, which revealed a growth of numerous fine processes between SGC envelopes and a 6-fold increase in the number of gap junctions [64,132] (Fig. 5).…”
Section: Plasticity Of Sgcsmentioning
confidence: 71%
“…However, dye coupling studies showed that SGCs around a given neuron are functionally coupled in about 21% of the cases [64,132] (see Fig. 3A).…”
Section: Gap Junctions In Sgcsmentioning
confidence: 99%
“…Moreover, axotomy also induces the hyperplasia of perineuronal satellite cells and triggers an incremented coupling in the lesioned DRG 23 . Likewise, Schwann cells react after axotomy both distally and proximally to the site of nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent studies have demonstrated that the satellite glial cells have the ability to regulate ion concentration and possess mechanisms for the release of cytokines, ATP and other chemical messengers like calcium. 8,9 SGCs are the consistent component of the DRG in all the species, yet their contribution to the basic neuronal functions remains relatively unknown. 10 SGCs have been reported to influence neuronal excitability the gap junctions.…”
Section: Introductionmentioning
confidence: 99%